DOUBLE CARBONATE BREAKDOWN REACTIONS AT HIGH PRESSURES: AN EXPERIMENTAL STUDY IN THE SYSTEM CAO-MGO-FEO-MNO-CO2 - Morlidge M.; Pawley A.; Droop G. (My University, 2006)
The pressure-temperature conditions of the reactions of the double carbonates CaM(CO3)2, where M = Mg (dolomite), Fe (ankerite) and Mn (kutnohorite), to MCO3 plus CaCO3 (aragonite) have been investigated at 5-8 GPa, 600-1,100°C, using multi-anvil apparatus. The reaction dolomite = magnesite + aragonite is in good agreement with the results of Sato and Katsura (Earth Planet Sci 184:529-534, 2001), but in poor agreement with the results of Luth (Contrib Mineral Petrol 141:222-232, 2001). The dolomite is partially disordered at 620°C, and fully disordered at 1,100°C. All ankerite and kutnohorite samples, including the synthetic starting materials, are disordered. The P-T slopes of the three reactions increase in the order M = Mg, Fe, Mn. The shallower slope for the reaction involving magnesite is due partly to its having a higher compressibility than expected from unit-cell volume considerations. At low pressures there is a preference for partitioning into the double carbonate of Mg > Fe > Mn. At high pressures the partitioning preference is reversed. Using the measured reaction positions, the P-T conditions at which dolomite solid solutions will break down on increasing P and T in subduction zones can be estimated. © Springer-Verlag 2006.
Keywords: ANKERITE; DOLOMITE; HIGH PRESSURE; HIGH TEMPERATURE; KUTNOHORITE; SUBDUCTION ZONES